2020
DOI: 10.1055/a-1148-2546
|View full text |Cite
|
Sign up to set email alerts
|

Moderators of the Association Between Serum Parathyroid Hormone and Metabolic Syndrome in Participants with Elevated Parathyroid Hormone: NHANES 2003–2006

Abstract: This cross-sectional study extracted data of 392 NHANES participants with elevated serum parathyroid hormone (PTH) concentrations from 2 cycles of the US National Health and Nutrition Examination Survey (NHANES) 2003–2006 and evaluated the association between serum (PTH) concentration and metabolic syndrome (MetS) to identify dietary and lifestyle factors that may modify that association. The primary outcome was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…There is evidence that high levels of calcium and low serum phosphorus (the biological aspects in primary hyperparathyroidism) alter the modulation of the insulin receptor, whereas excessive PTH concentration does not directly influence the insulin signal transduction pathway [ 146 ]. However, studies on patients without the diagnosis of primary hyperparathyroidism (such as NHANES cohort) showed that high serum PTH is positively correlated with the severity of metabolic syndrome if PTH is elevated at baseline [ 148 ].…”
Section: Pancreas-derivate Insulin Profile With Insulin Resistance An...mentioning
confidence: 99%
“…There is evidence that high levels of calcium and low serum phosphorus (the biological aspects in primary hyperparathyroidism) alter the modulation of the insulin receptor, whereas excessive PTH concentration does not directly influence the insulin signal transduction pathway [ 146 ]. However, studies on patients without the diagnosis of primary hyperparathyroidism (such as NHANES cohort) showed that high serum PTH is positively correlated with the severity of metabolic syndrome if PTH is elevated at baseline [ 148 ].…”
Section: Pancreas-derivate Insulin Profile With Insulin Resistance An...mentioning
confidence: 99%
“…There was no difference in the equipment, lab method, or lab site between the combined two survey cycles in our analysis. HP was defined as PTH > 65 pg/ml according to previous studies (1,41). The detailed process of measuring PTH was available at www.cdc.gov/nchs/nhanes/.…”
Section: Exposure and Outcome Definitionsmentioning
confidence: 99%